The Transformation of Written Communication through Artificial Intelligence: A Systematic Review and Analysis - Rini Susiani; Rahmi Fhonna; Barep Sarinauli; Ferlya Elyza (AL-ISHLAH: Jurnal Pendidikan, 2025)
The integration of artificial intelligence (AI) in language education has significantly influenced academic writing practices. Despite the growing adoption of AI tools, a comprehensive synthesis of their roles, benefits, and challenges in academic writing remains limited. This study conducted a systematic review following the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses – Scoping Review) framework. Articles published between 2019 and 2024 were sourced from ERIC and Google Scholar databases, focusing on the use of AI technologies in academic writing. A total of 28 eligible studies were reviewed and analyzed. The findings highlight three dominant AI tools: QuillBot (30%), Grammarly (25%), and ChatGPT (15%), each contributing across domains such as language enhancement, content generation, and translation. These tools are widely used to improve grammar, paraphrasing, writing structure, and provide immediate, adaptive feedback. The implementation spans various stages of the writing process, from prewriting to revision. While AI tools offer significant educational benefits—including improved writing quality, personalized learning, and efficiency—they also present challenges. These include over-reliance, reduced critical thinking, concerns about academic integrity, and data privacy risks. The review emphasizes the importance of pedagogically grounded AI integration to maintain student autonomy and uphold academic ethics. This review offers a practical framework for integrating AI in academic writing instruction, balancing technological affordances with essential educational values. It provides actionable insights for educators to support ethical and effective AI use in writing pedagogy.